Unit-level Digital Twin Model Construction Technology for Part Manufacturing Processes - LI Dong; LIN Zhiwen; CHEN Chuanhai; ZHAO Yongsheng; LIU Zhifeng (Journal of Harbin University of Science and Technology, 2025)
The application of digital twin technology in manufacturing is becoming increasingly widespread, particularly in the machining process of parts. Constructing high-fidelity digital twin models of manufacturing units is crucial for optimizing quality control and decision-making in machining processes. This paper reviews the construction technology of unit-level digital twins for part machining, focusing on three key aspects: virtual entity model construction, process strategy design, and process parameter decision making. The current research status and limitations of these aspects in both domestic and international contexts are discussed. A corresponding technical implementation framework is proposed. Through a case study of machining a cavity test specimen, the implementation effectiveness of unit-level digital twin construction technology in part machining is demonstrated and compared with traditional machining methods in terms of efficiency. Finally, the challenges in achieving unit-level digital twins and future development directions are summarized.